Increasing Student Learning Activeness In Civic Education Using Ice Breaking For Grade I Students Of SD Negeri 01 Pojok - Kaswanti, Dwi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study aims to increase student learning activeness in Civic Education by using ice breaking for grade I students of SDN 01 Pojok. This type of research is Classroom Action Research. Data collection methods used are observation, questionnaires, and interviews. Based on the results of the study it can be concluded that the use of ice breaking can increase that can be seen from the activeness of students in: (1) being able to answer questions posed by the teacher/other students from 21.42% before the action to 64.28% after the action, (2) actively asking the teacher about the material being studied from 42.85% before the action to 85.71% after the action, (3) able representing the group in presenting the results of group discussions from 35.71% before the action to 64.28% after the action, (4) Actively discussing in groups from 35.71% before the action to 78.57% after the action, (5) closely observing the teacher's explanation from 57.14% before the action to 78.57% after the action, (6) Raising hands to answer practice questions from 35.71% before the action to 85.71% after the action, (7) Giving responses to questions answered by friends from 28.57% before the action to 78.57% after the action. The conclusion of this study is that the use of ice breaking in learning Pancasila Education can increase student learning activeness.